Evaluation of biomolecular interactions and cytotoxic activity of organometallic binuclear Ru(II) complexes of ferrocenyl thiosemicarbazones - Khanvilkar, Priyanka; Dash, Soumya R.; Vohra, Alisagar; Devkar, Ranjitsinh; Chakraborty, Debjani (Journal of Biomolecular Structure & Dynamics, 2020)
{Four new ferrocenyl substituted thiosemicarbazone ligands (L1-L4) and their corresponding binuclear ruthenium(II) arene complexes of the general type [(eta(6)-pcym)(L)Ru(mu-im)Ru(L)(eta(6)-p-cym)]Cl (C1-C4) and [(eta(6)-pcym)(L)Ru(mu-azpy)Ru(L)(eta(6)-p-cym)]Cl-2(C5-C8) (cym = cymene
Keywords: binuclear ruthenium(II) complexes; BSA binding interactions; DNA; Ferrocenyl thiosemicarbazone; HeLa human cervical carcinoma

Imidazole/4,4 `-azopyridine bridging binuclear Ru(II) complexes: design, synthesis, bimolecular interactions and cytotoxicity against HeLa cell line - Khanvilkar, Priyanka; Dash, Soumya R.; Pulipaka, Ramadevi; Shirsath, Kavita; Devkar, Ranjitsinh; Chakraborty, Debjani (Journal of the Iranian Chemical Society, 2021)
Binuclear Ru(II)-arene complexes [(eta(6)-pcym)(Flq)Ru(mu-im/mu-azpy)Ru(Flq)(eta(6)-p-cym)]Cl (C1-C8) (cym = cymene; Flq = fluoroquinolones; im = imidazole; azpy = 4,4 ` azo pyridine) have been synthesized and characterized by elemental analysis, molar conductivity and various spectral techniques (ESI-MS, IR, UV-Vis and H-1-NMR). The geometry of the complexes was optimized by DFT calculations, which revealed a pseudo-octahedral coordination around each metal centre. Binding of the synthesized complexes with CT-DNA and BSA was studied spectroscopically, and it has been established that the presence of two hydrophobic planar arene moieties enhances the binding efficacies of the binuclear complexes to the macromolecules, compared to their mononuclear analogues. The results of competitive binding between C1-C8 and ethidium bromide (EB) towards DNA have shown that the complexes are able to displace EB from DNA-EB adduct and interact with DNA via intercalation. The complexes display cytotoxicity against the HeLa human cervical cancer cell lines with IC50 values in the range of 30.1-120.9 mu M.
Keywords: Binuclear ruthenium (II) complexes; BSA binding interactions; DFT calculations; DNA; Fluoroquinolones (FQs); HeLa human cervical carcinoma

Organoruthenium (II) complexes featuring pyrazole-linked thiosemicarbazone ligands: synthesis, DNA/BSA interactions, molecular docking, and cytotoxicity studies - Khanvilkar, Priyanka; Dash, Soumya R.; Banerjee, Devjani; Vohra, Aliasgar; Devkar, Ranjitsinh; Chakraborty, Debjani (Applied Organometallic Chemistry, 2021)
A series of pyrazol-derived thiosemicarbazone ligands (L1-L4) were synthesized and reacted with [Ru(p-cymene)(mu-Cl)Cl](2) to yield a series of ``piano-stool''-type binuclear ruthenium (II)-arene-thiosemicarbazone complexes (C1-C8) of the general type [(Ru(eta(6)-p-cym)L)(2)(mu-im/azpy)] Cl1-2 (L = diphenylpyrazole thiosemicarbazone; cym = p-cymene; im = imidazole; azpy = 4,4 `-azopyridine). The thiosemicarbazone ligands act as N and S donors binding to the Ru(II) center via the imine nitrogen and the thione sulfur atoms. The complexes were characterized by NMR, FTIR, UV-Vis spectroscopy, and ESI+ mass spectrometry. The binding of the complexes to calf thymus deoxyribonucleic acid (CT-DNA) and bovine serum albumin (BSA) was evaluated, and it has been established that the binuclear complexes have good binding efficacies with DNA (K-b = 10(4)-10(5) M-1) and BSA (K-a = 10(5)-10(6) M-1). This is attributed to the arene moieties present in the ligands of the complexes that can have hydrophobic interactions with DNA/BSA. Ethidium bromide (EB) displacement studies and DNA viscosity measurements revealed intercalative interaction of the complexes with DNA. Static interaction of the complexes with BSA was revealed by fluorescence quenching studies. Molecular docking studies confirmed base stacking, H-bonding, and hydrophobic interactions with the biomolecules. In vitro antiproliferative studies of the complexes affirmed that the complexes are cytotoxic towards the HeLa (human cervical cancer) cell line with IC50 values in range of 17.3-41.3 mu M.
Keywords: Binuclear ruthenium (II) complexes; BSA binding interactions; DNA; HeLa human cervical carcinoma; pyrazole-derived thiosemicarbazone

Reactivity of four coordinate iridium complex towards hydrogen: an experimental and computational study - Agrawal, Nisha K.; Dash, Soumya R.; Vanka, Kumar; Nethaji, Munirathinam; Jagirdar, Balaji R. (Journal of Organometallic Chemistry, 2022)
Reaction of a four coordinate, 16-electron Ir complex, [Ir-(iPr)4(POCOP)(PPh3)] (4 ) (((iPr)4)(POCOP= 2,6-bis(di-isopropyl phosphinito)benzene, kappa(3)-C6H3-1,3-[OP((iPr))(2)](2)), with H-2 resulted in an oxidative addition product, cis-dihydride complex, cis-[Ir(H)(2) ((iPr)4)(POCOP)(PPh3)] ( cis-5 ) presumably via the intermediacy of a sigma complex, [Ir(eta(2)-H-2)((iPr)4)(POCOP)(PPh3)]. The cis-dihydride complex completely isomerizes to the trans-dihydride complex trans-[Ir(H)(2) ((iPr)4)(POCOP)(PPh3)] ( trans-5 ) under ambient conditions in about 3 h. It was found that the steric and electronic features on the iridium center have significant influence on the approach of H-2 onto the metal center followed by oxidative addition and isomerization. The isomerization process was studied in detail and all the mechanistic aspects have been elucidated using a combination of both experimental work and computation. The cis-dihydride complex isomerizes to the trans-dihydride by compensating the trans influence of the strongly trans-directing hydride ligand. A mechanism involving the exchange of the position of PPh3 with a hydride ligand cis to itself via PPh3 dissociation and re-coordination thereby resulting in the formation of the trans-dihydride complex, has been proposed for the isomerization. The cis-dihydride was found to be a highly active catalyst for hydrogenation of ethy-lene. A competing reactivity study of cis-dihydride between isomerization versus insertion of C2H4 into the Ir-H bond, was studied experimentally and computationally. (c) 2022 Elsevier B.V. All rights reserved.
Keywords: Hydrogenation; Insertion; iridium complex; isomerization; Oxidative addition; Reductive elimination

Dual routes toward observation of a trans-H2/hydride complex in an iridium pincer system and hydrogenation catalytic activity - Agrawal, Nisha K.; Dash, Soumya R.; Vanka, Kumar; Jagirdar, Balaji R. (Organometallics, 2023)
The Abstraction of chloride from a six- coordinate complex, trans-[ Ir(H)(Cl)((iPr)4)(POCOP)(PPh3)] (1) [((iPr)4)(POCOP) = 2,6-bis(di-iso-propylphosphinito)benzene,kappa(3)-C6H3-1,3-[OP(Pr-i)(2 )](2)], using NaBAr4f leads to the generation of a dinitrogen complex, trans-[Ir(H)(N-2)((iPr)4)(POCOP)(PPh3)][BAr4f] (6). Addition of H-2 to [Ir(H)(N-2)((iPr)4)(POCOP)(PPh3)](+) (6) under extremely mild conditions (1 bar, 298 K) resulted in the reversible coordination of H-2 to generate the cis-[Ir(H)(eta H-2-(2))((iPr)4)(POCOP)(PPh3)](+) (cis-11) complex. The cis-[Ir(H)(eta(2)-H-2)((iPr)4)(POCOP)(PPh3)](+) complex (cis-11) isomerized to a trans isomer, trans-[Ir(H)(eta(2)-H-2)((iPr)4)(POCOP)(PPh3)](+) (trans-11), at 253 K. The isomerization process has been studied and supported by computations. Employing an alternative route, protonation of the trans-[Ir(H)(2)((iPr)4)(POCOP)(PPh3)] complex (2) at 183 K resulted in the formation of an identical, trans-[Ir(H)(eta(2)-H-2)((iPr)4)(POCOP)(PPh3)](+) complex (trans-11); upon warming the sample, the trans-H-2/hydride complex isomerized to the cis isomer above 253 K. Two independent routes to obtain trans-[Ir(H)(eta(2)-H-2)((iPr)4)(POCOP)(PPh3)](+) (trans-11) species have been established. Reaction of trans-[Ir(H)(N-2)((iPr)4)(POCOP)(PPh3)][BAr4f] (6) with C2H4 gave the cis-[Ir(H)(eta(2)-C2H4)((iPr)4)(POCOP)(PPh3)](+) complex (cis-15), which also undergoes isomerization to yield an equilibrium mixture of cis/trans-[Ir(H)(eta(2)-C2H4)((iPr)4)(POCOP)(PPh3)](+) complexes (cis-15 and trans-15) at 253 K. The trans-[Ir(H)(N-2)((iPr)4)(POCOP)(PPh3)](+) complex (6) is an excellent catalyst for hydrogenation of ethylene to ethane under very mild conditions.

H-atom site exchange in an iridium trans-dihydrogen/hydride complex, trans-[Ir(H)(?2-H2)(iPr)4(POCOP)(DMAP)]+ - Agrawal, Nisha K.; Gayathridevi, S.; Dash, Soumya R.; Vanka, Kumar; Jagirdar, Balaji R. (Dalton Transactions, 2023)
Treatment of trans-[Ir(H)(N)(2)((iPr)4)(POCOP)(DMAP)][BAr4f] (2) with H-2 (1 bar) under ambient conditions (298 K) results in the formation of a trans-[Ir(H)(?(2)-H-2)((iPr)4)(POCOP)(DMAP)][BAr4f] (3) complex. Complex 3 exhibits H-atom site exchange between the bound H-2 and the hydride ligands which are mutually trans to one another. A plausible mechanism of this exchange involves metal-ligand cooperativity as studied by computations.

Crystal engineering for intramolecular π-π stacking: effect of substitution of electron-donating and electron-withdrawing groups on the molecular geometry in conformationally flexible Sulfoesters and sulfonamides - Shaikh, Samir R.; Gawade, Rupesh L.; Dabke, Niteen B.; Dash, Soumya R.; Vanka, Kumar; Gonnade, Rajesh G. (CrystEngComm, 2024)
A series of 21 sulfoester and sulfonamide derivatives comprising two aromatic rings was synthesized to investigate the effect of the presence of either electron-donating (ED) or electron-withdrawing (EW) groups on the intramolecular pi-stacking assembly. The positioning of ED or EW moieties was carried out directly on one of the aromatic rings linked to the sulfonyl or sulfonamide moieties. In contrast, the other aromatic ring (phenyl or pyridine) was connected by a -CH2-CH2- spacer with the sulfonyl or sulfonamide moiety. The purpose of having an ethyl spacer between the two aromatic rings was to achieve conformational flexibility, facilitating the intramolecular pi-stacking assembly between the two aromatic rings. The use of sulfoester/sulfonamide groups allowed more conformational flexibility to attain desired orientations in solids with the interplay of the hydrogen-bonding interactions. Between the two functional groups, sulfonamides offered a more hydrogen-rich environment due to the amine moiety and may exhibit higher H-bonding propensity than the sulfoester moiety. The central idea here was to study the interplay between the hydrogen-bonding and pi & ctdot;pi interactions. The substituent groups chosen were categorized as strong electron-withdrawing (-CF3 and -CN), weak electron-withdrawing (-Cl and -Br), neutral (-H), and good electron-donating (-CH3 and -OCH3) groups. Crystal structure analysis revealed the syn conformation for all the derivatives, enabling intramolecular pi & ctdot;pi interactions between the two aromatic rings, whereas in the sulfonamide derivatives, the molecule takes either midway or anti conformations, except for one pyridine sulfonamide derivative, which showed the syn orientation but lacked intramolecular pi-stacking interactions. The absence of any conventional H-bond forming functional groups in the sulfoester derivatives may have resulted in the syn geometry facilitated by intramolecular pi-stacking interactions. Conversely, H-bond-forming functional groups in the sulfonamide derivatives could have prevented the syn conformation. The conformational analysis carried out employing density functional theory (DFT) calculations confirmed the higher stability of the syn conformation over the midway and anti orientations. The placing of electron-withdrawing and electron-donating groups at the para position of the benzene revealed sulfoesters preferably adopts a syn geometry facilitating the intramolecular pi-stacking, but sulphonamides takes midway or anti-geometry.

Designing of imine thiophene-ligated metal-complexes and implication in ethylene polymerization - Shaikh, Maulali H.; Ramekar, V. Rohan; Jawoor, Shailaja; Dash, Soumya R.; Birajadar, Rajkumar S.; Pawal, Sandip B.; Thenmani, Nandakumar; Vanka, Kumar; Chikkali, Samir H. (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2024)
Polyethylene is the single largest volume polymer produced globally using Ziegler-type catalysts. Numerous modifications have been reported in search of a better catalyst that can control molecular weight, polydispersity, and branching. In our attempts to identify a suitable imine thiophene-ligated chromium complex, we examined 9 different titanium complexes computationally. The DFT investigations considered barriers for insertion, propagation, and termination by beta-H elimination or chain transfer, and identified N-(4-methoxyphenyl)-2-phenyl-1-(thiophen-2-yl)ethan-1-imine(L9) as the most suitable ligand. Subsequently, L9 was prepared in good yield (70%) by condensing 2-phenyl-1-(thiophen-2-yl)ethan-1-one with 4-methoxyaniline. Ligand L9 was treated with early transition metal precursors (Ti, Cr, Zr) to generate a homogenous catalyst. The identity of these catalysts was unambiguously ascertained using a combination of NMR, ICP, FT-IR, UV-Vis spectroscopy, and ESI-MS. The performance of L9-ligated titanium complex [Cat.1] was examined in ethylene polymerization using MMAO as a co-catalyst. Insertion of ethylene was tracked using high-pressure NMR experiments and Cat.1 was found to be active in the polymerization. Ethylene polymerization conditions were optimized to obtain high activity and molecular weight polyethylene. The chromium complex [Cat.2] outperformed the Ti and Zr-derived catalysts with the highest TOF of 6294 mol of PE/mol of Cr/h. Cat.2 produced high molecular weight, high-density polyethylene.
Keywords: Cr-complexes; DFT; high-density polyethylene; Imine thiophene ligand; Polyethylene

Synthesis and concomitant polymorphs of green fluorescence protein chromophore-anthracene-based fluorescent analogue - Mali, Bhupendra P.; Dabke, Niteen B.; Dash, Soumya R.; Biswas, Anupam; Vanka, Kumar; Manoj, Kochunnoonny; Gonnade, Rajesh G. (Crystal Growth & Design, 2025)
Controlled variations in fluorescence properties hold significant promise for applications in optical sensors, bioimaging, and advanced display devices. However, constructing multicolor fluorescent systems remains a challenge. In this study, we demonstrate the development of multicolor fluorescence by generating polymorphs of a novel green fluorescent protein chromophore analogue, which exhibits distinct photoluminescence emissions in the solid state. The observed emission variations are attributed to differences in molecular conformation due to variations in pi-stacking interactions between the polymorphs. This offers a novel approach to designing materials with tunable fluorescence properties.